Religiosity of Gadget-Addicted Children: Case Study In Southern Thailand - Saman, Miss Fatihah; Afifa, Erlina Laily Nur; Candrika, Ariibah Radita Ayu; Ikhrom, Ikhrom; Junaedi, Mahfud (UMSU, 2025)
This study aims to examine the impact of gadget addiction on the religious morality of Muslim children in Southern Thailand. The phenomenon has emerged alongside the rapid development of digital technology and the increasing integration of gadgets into children’s daily lives. The primary objective of the research is to identify the factors contributing to the decline in children’s interest in religious activities, the rise of disobedience toward parents, and the decreasing participation in religious education. The study employed a qualitative case study approach, conducted in La’al Village, Saiburi, Pattani, with research subjects consisting of fifth and sixth-grade elementary school students. Data were collected through interviews and documentation, then analyzed descriptively using data reduction, data presentation, and conclusion drawing. The findings indicate that gadget addiction significantly affects children’s spiritual, moral, and social development. Excessive gadget use leads to neglect of religious obligations, weakened ethical interactions with parents, and reduced involvement in religious education.